The Research of G–Motif Construction and Chirality in Deoxyguanosine Monophosphate Nucleotide Complexes - Zhu, Yanhong; Li, Zhongkui; Wang, Pengfei; Qiu, Qi–Ming; Ma, Hongwei; Li, Hui (Frontiers in Chemistry, 2021)
A detailed understanding of the mismatched base-pairing interactions in DNA will help reveal genetic diseases and provide a theoretical basis for the development of targeted drugs. Here, we utilized mononucleotide fragment to simulate mismatch DNA interactions in a local hydrophobic microenvironment. The bipyridyl-type bridging ligands were employed as a mild stabilizer to stabilize the GG mismatch containing complexes, allowing mismatch to be visualized based on X-ray crystallography. Five single crystals of 2′-deoxyguanosine–5′–monophosphate (dGMP) metal complexes were designed and obtained via the process of self-assembly. Crystallographic studies clearly reveal the details of the supramolecular interaction between mononucleotides and guest intercalators. A novel guanine–guanine base mismatch pattern with unusual (high anti)–(high anti) type of arrangement around the glycosidic angle conformations was successfully constructed. The solution state 1H–NMR, ESI–MS spectrum studies, and UV titration experiments emphasize the robustness of this g–motif in solution. Additionally, we combined the methods of single-crystal and solution-, solid-state CD spectrum together to discuss the chirality of the complexes. The complexes containing the g–motif structure, which reduces the energy of the system, following the solid-state CD signals, generally move in the long-wave direction. These results provided a new mismatched base pairing, that is g–motif. The interaction mode and full characterizations of g–motif will contribute to the study of the mismatched DNA interaction.